Indonesian Port as a Control of State’s Econom - Tungkup, Doharman Lumban (IWTJ : International Water Transport Journal, 2020)
The main objective of each port is to meet the needs of port customers. In general, port service customers need facilities and services for ships, goods, goods, passengers, and land transportation can be carried out effectively and efficient. So there is a close connection between ports and ships as a service user, because the port is a working environment where ships can dock safely and cheaply, avoiding the dangers threatening the ship engulfed by waves, wind and so on, deep carry out activities to unload goods, animals and passengers. A port can be said to be effective and efficient if the ship does not wait long at sea, it can loading and unloading quickly and smoothly and supported by facilities adequate equipment or facilities and infrastructure, because it is very important for shipping companies. It is the duty of ports to contribute foreign exchange to the State.